Short vs. Standard Laser‐Microgrooved Implants Supporting Single and Splinted Crowns: A Prospective Study with 3 Years Follow‐Up. Issue 2 (31st August 2018) - Guarnieri, Renzo; Di Nardo, Dario; Gaimari, Gianfranco; Miccoli, Gabriele; Testarelli, Luca
Abstract: Purpose: The aim of this study was to compare survival rates, marginal bone loss (MBL), and peri‐implant soft tissue parameters between short and standard laser‐microgrooved implants supporting single or splinted crowns 3 years after loading. Materials and Methods: 30 subjects received 1 short ( ≤ 7 mm ) and 1 standard length ( ≥ 9 mm ) laser‐microgrooved implant in adjacent sites of the premolar and molar regions of the mandible or maxilla. Peri‐implant soft tissue parameters and intraoral radiographs were recorded at the delivery of definitive crowns (baseline) and 3 years later. Cumulative survival rate (CSR) and marginal bone loss (MBL) in relation to crown/implant (C/I) ratio, implant length, location, type of antagonist, and type of prosthetic design (single or splinted), were evaluated. Results: CSR of short implants was 98%, compared to 100% for standard implants, without significant statistical difference. MBL was not significantly different over the observation period, with an average of 0.23 ± 0.6 mm and 0.27 ± 0.3 mm for short and standard implants, respectively. No statistical differences were found between short and standard implants regarding plaque (14.7% vs. 15.7%), number of sites BOP (8.3% vs. 5.9%), probing depth (1.13 ± 0.6 mm vs. 1.04 ± 0.8 mm), and mean mucosal recession (0.18 ± 0.3 mm vs. 0.22 ± 0.3 mm). Analyzing MBL in relation to the C/I ratio, implant length, location, type of antagonist, and type of prosthetic design, no statistically significant differences were found. Conclusion: Regardless of C/I ratio, implant length, location, type of antagonist, and type of prosthetic design, short and standard laser‐microgrooved implants had similar survival rates, MBL, and peri‐implant soft tissue conditions over the observation period of 3 years.